2017
DOI: 10.1097/md.0000000000007793
|View full text |Cite
|
Sign up to set email alerts
|

Causes of hematochezia and hemorrhagic antibiotic-associated colitis in children and adolescents

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(63 reference statements)
0
13
0
1
Order By: Relevance
“…In a study of children aged 0–2 years that included 6,625 diarrheal stool specimens, adenovirus detection was similar in children with and without blood in their stools 37 . Although norovirus was detected in specimens from only 4.5% of children and adolescents with hematochezia in Austria, 2 a study of norovirus‐associated gastroenteritis in Brazil reported the presence of hematochezia in over 10% of children and adults 38 . These findings are in‐keeping with our detection of norovirus in 11.3% of children with hematochezia.…”
Section: Discussionmentioning
confidence: 98%
“…In a study of children aged 0–2 years that included 6,625 diarrheal stool specimens, adenovirus detection was similar in children with and without blood in their stools 37 . Although norovirus was detected in specimens from only 4.5% of children and adolescents with hematochezia in Austria, 2 a study of norovirus‐associated gastroenteritis in Brazil reported the presence of hematochezia in over 10% of children and adults 38 . These findings are in‐keeping with our detection of norovirus in 11.3% of children with hematochezia.…”
Section: Discussionmentioning
confidence: 98%
“…The principal virulence factors of Clostridium di cile (C.di cile), toxins A, B and ADP-ribosyltransferase (CDT) 37 , are the main causes of pseudomembranouscolitis 24 ,accounting for 15-25% of the antibioticassociated bloody diarrhea (AABD) inpatients 38 , especially in the aging population 22 . However, only 14% C.di cile infection presents bloody stools 39 . The morbidity rate of AAC increased because most patients developed secondary infection withC.di cile 3 .…”
Section: Treatment and Follow-up Resultsmentioning
confidence: 99%
“…AAC might be caused by other pathogens in addition to K.oxytocaor C.di cile 39 .StampfeLet al 39 reported AAC:antibiotic associated colitis; AAHC:antibiotic associated hemorrhagic colitis; CNKI:Chinese national knowledge infrastructure; WBC:white blood cell count; HGB:The laboratory tests for hemoglobin; RBC: red blood cell count; ESR:erythrocyte sedimentation rate; CRP:C-reactive protein; CT:computed tomography; K. oxytoca:Klebsiella oxytoca; OB:occult blood; CDT:ADP-ribosyltransferase; AABD:antibiotic-associated bloody diarrhea.…”
Section: Treatment and Follow-up Resultsmentioning
confidence: 99%
“…Apart from autoimmunity, pathogens also exploit the role of indole metabolism in maintaining homeostasis in the host. The pathobiont Klebsiella oxytoca secretes the indole analog tilivalline to induce antibiotic-associated hemorrhagic colitis (Stampfer et al, 2017). Substantially simplified tilivalline mimics block the production of tilivalline (von Tesmar et al, 2018).…”
Section: Downloaded Frommentioning
confidence: 99%